2001
DOI: 10.1002/mus.1219
|View full text |Cite
|
Sign up to set email alerts
|

Ventral polyradiculopathy with pediatric acute lymphocytic leukemia

Abstract: A 3-year-old girl with acute lymphocytic leukemia (ALL) in remission developed lower extremity paraparesis and areflexia 15 days after receiving intrathecal methotrexate, cytarabine, and hydrocortisone. Cerebrospinal fluid protein was 107 mg/dl. Compound muscle action potential amplitudes were reduced, F waves were absent, and sensory conduction studies were normal. Needle electromyography (EMG) revealed reduced motor unit potential recruitment. Magnetic resonance imaging (MRI) showed lumbosacral ventral root … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Potential rare complications of ITM therapy are leukoencephalopathy [12,13], encephalomyelopathy [14,15], lumbosacral polyradiculopathy [3,4], neurogenic pulmonary oedema and sudden death [16]. A subacute anterior lumbosacral polyradiculopathy was the cause of progressive flaccid paraparesis without sensory level in our patient.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Potential rare complications of ITM therapy are leukoencephalopathy [12,13], encephalomyelopathy [14,15], lumbosacral polyradiculopathy [3,4], neurogenic pulmonary oedema and sudden death [16]. A subacute anterior lumbosacral polyradiculopathy was the cause of progressive flaccid paraparesis without sensory level in our patient.…”
Section: Discussionmentioning
confidence: 91%
“…A subacute anterior lumbosacral polyradiculopathy was the cause of progressive flaccid paraparesis without sensory level in our patient. Clinic cases of ITC-related polyradiculopathy have been previously described as motor syndromes in children, with good recovery after several days to weeks [3,4]. CSF examination reveals mild to moderate elevation of protein, with or without immunoglobulin synthesis.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…[3][4][5][6][7][8] Since 1987 to 2014 a total of 9 children with ALL aged 3-7 years developed neurologic symptoms. The majority (7/9) were boys.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation is that some agents injure the ventral nerve roots more strongly than the dorsal roots. Anderson et al [8] reported the case of a 3-year-old girl diagnosed with acute lymphoblastic leukaemia who developed subacute anterior lumbosacral polyradiculopathy following intrathecal methotrexate. Her spinal MRI revealed Case report: Gadolinium enhancement of cauda equina…”
Section: Discussionmentioning
confidence: 99%